Pengembangan Buku Ajar Bergambar Berbasis Karakter Profetik - KAMIM TOHARI; Retno Intan Kuswari; Riyanto, Riyanto (STAI KH. Muhammad Ali Shodiq, 2023)
Abstract This research is motivated by the fact that there have not been many innovations made by teachers in developing illustrated textbooks as learning media. Whereas innovation in learning is a necessity so that the teaching and learning process is more varied and not boring. One of the innovations referred to in this study is the development of textbooks. The development of prophetic character-based illustrated textbooks is expected to contribute to supporting the teaching and learning process, stimulating the spirit of learning, and instilling prophetic character in students. This research reviews how to develop picture teaching books that contain their advantages, and the effectiveness of learning outcomes after using this prophetic character-based picture book. The purpose of this research is to develop prophetic character-based picture teaching books, describe their advantages, and find out the learning outcomes of students after using them. This research uses Reseacrh and Development referring to the Borg and Gall model. In collecting data, researchers used qualitative and quantitative data. The results showed that there is an interesting prophetic character-based picture teaching book that has implications for the enthusiasm for learning and student learning outcomes. Keywords: Picture Textbook, Prophetic Character, Development